Design Of Data Acquisition And Electrical Equipment Controller Systems In Classroom Arduino Mega And NodeMCU ESP8266 Based - Minarto Minarto; Imay Kurniawan; Candra Dewi Lestari; Lise Sri Andar Muni (RISTEC : Research in Information Systems and Technology, 2023)
The method of class preparation in tertiary institutions especially in Purwakarta Regency still uses conventional methods. At Purwakarta Wastukancana College of Technology, conventional Â class preparation activities have a problems. An electricequipment being turned on too early and also the possibility of a delay in turning it off, this could result in the use of inefficient electrical equipment and also an effect on electricity costs.The authors conducted research with the aim of designing and building a system that functions to acquire and control electrical devices in the form of lamps and air conditioners in desktop-based classrooms with the method of developing Pressman waterfall 2010, designing models using a unified modeling language (UML) ) namely use case diagrams, activity diagrams, sequence diagrams, and class diagrams. Built using the PHP programming language and Visual Basic.Net, for databases using MySQL, and testing applications using black-box testing, for hardware implementation, the authors use Arduino Mega, Nodemcu ESP8266.With the creation of a data acquisition system and control of classroom arduino mega and nodemcu esp8266 electrical devices for the Purwakarta Wastukancana College of Technology will advance the means for regulating the use of electricity, thereby increasing electricity efficiency. Furthermore, it can provide cost efficiency in electricity payments.Â Keywords: Data acquisition, monitoring system, application, Waterfall, Arduino mega, Nodemcu ESP8266, MySQL.